Belfast after 1994 Narrating the Troubles in Post-Ceasefire Film - Schwerter, Stephanie (ABEI Journal, 2017)
The project carried out as an associate researcher of the W. B. Yeats Chair of Irish Studies at University of São Paulo is part of an ongoing book project entitled “Framing Division. Belfast, Beirut and Berlin in Contemporary Film”. Following a comparative approach, I set out to explore the cinematographic representation of three cities famous for their different internal boundaries. Films focussing on Belfast shall be analysed in comparison to feature films dealing with Berlin during the Cold War and Beirut during the Civil War.